'Not one action but many': institutional work by commissioners of children's mental health services in the English NHS. Issue 3 (22nd November 2020) - Passey, Andrew
Abstract: This article enhances our understanding of institutional work, through a study of professional health commissioners in the English National Health Service. Using a case study of mental health policy implementation, commissioners are conceptualized as institutional agents involved in shaping the organizational field and its boundary. Health service commissioners face a series of challenges as institutional agents. Commissioning is a relatively new health profession. It lacks a strong professional association and has predominantly been externally professionalized. Commissioners have limited direct organizational strategic management control. In the case study, commissioners were charged with leading implementation of the policy, which required them to address fragmentation in the field. Using existing typologies as an analytical frame, activities by commissioners in the case study are identified and explored as different modes of institutional work. Commissioners created a new normative network and instigated specific processes to embed and routinize cross-organization working. They undertook boundary-spanning cognitive institutional work, creating new knowledge by commissioning education of school staff in the basics of children's mental health. Their institutional work involved challenging existing working practices, both in the health field and in the contiguous education field. The article elucidates connections between different modes of institutional work and attends to boundary work by commissioners in parallel with institutional work in the field. It also outlines how a profession seemingly lacking many of the ingredients of institutional power might pursue its own professional project through institutional work. Findings have resonance in other geographical and policy areas and fields.